2017
DOI: 10.1007/s00018-017-2715-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages targeting intestinal epithelial cells: a potential novel form of immunotherapy

Abstract: In addition to their established role as a physical barrier to invading pathogens and other harmful agents, intestinal epithelial cells (IEC) are actively involved in local immune reactions. In the past years, evidence has accumulated suggesting the role of IEC in the immunopathology of intestinal inflammatory disorders (IBD). Recent advances in research on bacteriophages strongly suggest that—in addition to their established antibacterial activity—they have immunomodulating properties that are potentially use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 62 publications
2
18
0
1
Order By: Relevance
“…In the face of increasing drama of anti-microbial resistance, phages offer a broad medical promise as a weapon against antibiotics-resistant bacteria [10]. However, phages should no longer be considered as mere bacterial viruses but also as potential modulators of immunity [11][12][13][14][15][16], a finding which may have an important application in therapy including autoimmune diseases [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the face of increasing drama of anti-microbial resistance, phages offer a broad medical promise as a weapon against antibiotics-resistant bacteria [10]. However, phages should no longer be considered as mere bacterial viruses but also as potential modulators of immunity [11][12][13][14][15][16], a finding which may have an important application in therapy including autoimmune diseases [12].…”
Section: Introductionmentioning
confidence: 99%
“…22 Intestinal epithelial cells cannot easily maintain intestinal absorption and defense functions. 23 Our results demonstrated that the intestinal crypt-villus structure in XH-105-treated mice was well preserved after 9.0 Gy TBI. The intestinal epithelium is one of the most rapidly self-renewing organizations in mammals and is continuously renewed by intestinal epithelial stem cells located in the crypts.…”
Section: Discussionmentioning
confidence: 50%
“…Bacteriophages (or “phages” for short) can multiply only in bacterial cells, are detectable wherever live bacteria exist, and can be isolated from all environments. It is estimated that phages outnumber bacteria by an order of magnitude (Gorski et al, ); therefore, the role of phages in intestinal homeostasis cannot be ignored. Regulation of bacteria‐phage interactions and resulting phage‐specific infection can account for up to 80% of total bacterial mortality in a given ecosystem, thereby greatly affecting bacterial diversity and function (De Sordi, Lourenco, & Debarbieux, ; Mirzaei and Maurice ; Scanlan, ).…”
Section: Interaction Of Silver Nanoparticles With Phages and Gut Micrmentioning
confidence: 99%